Structure of gut microbiota and characteristics of fecal metabolites in patients with lung cancer - Lu, Xingbing; Xiong, Li; Zheng, Xi; Yu, Qiuju; Xiao, Yuling; Xie, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
•We combined multi-omics to find changes in the composition of the gut microbiome in clinical lung cancer patients, characterized by a decrease in Probiotics and an overgrowth of potentially pathogenic bacteria.•We are the first to study the relationship between lung cancer and the gut microbiota and its metabolite population, supporting the hypothesis that changes in specific microbiota influence the development of lung cancer. We suggest that decreasing levels of Firmicutes and Lachnospira and increasing levels of Ruminococcus gnavus group are associated with lung cancer.•We found that most metabolites were closely associated with the characteristic microbiome and that metabolism is attenuated in lung cancer patients, such as quinic acid, 3-hydroxybenzoic acid,1-methylhydantoin,3,4-dihydroxydrocinnamic acid and 3,4-dihydroxybenzeneacetic acid, and the five metabolites most closely associated with lung cancer showed a decreasing trend in lung cancer patients.